2016
DOI: 10.1037/pas0000172
|View full text |Cite
|
Sign up to set email alerts
|

Measuring implicit attitudes: A positive framing bias flaw in the Implicit Relational Assessment Procedure (IRAP).

Abstract: How can implicit attitudes best be measured? The Implicit Relational Assessment Procedure (IRAP), unlike the Implicit Association Test (IAT), claims to measure absolute, not just relative, implicit attitudes. In the IRAP, participants make congruent (Fat Person-Active:False; Fat Person-Unhealthy: True) or incongruent (Fat Person-Active: True; Fat PersonUnhealthy: False) responses in different blocks of trials. IRAP experiments have reported positive or neutral implicit attitudes (e.g., neutral attitudes toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
(107 reference statements)
1
12
0
1
Order By: Relevance
“…It seems plausible to consider that the orienting function of the response option true may have been stronger than the orienting function of false ( true may have a stronger orienting function since it frequently serves as a confirmatory, favorable, or positive response in natural language). Indeed, previous research (e.g., O’Shea et al, 2016) has shown that participants may find it easier to respond true to positive stimuli than to press false , if these are the IRAP response options. Based on the current results, it is possible to suggest that a behavioral bias to relate happy faces and true have emerged in the course of the IRAP trial types that presented such a combination (i.e., trial-types 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible to consider that the orienting function of the response option true may have been stronger than the orienting function of false ( true may have a stronger orienting function since it frequently serves as a confirmatory, favorable, or positive response in natural language). Indeed, previous research (e.g., O’Shea et al, 2016) has shown that participants may find it easier to respond true to positive stimuli than to press false , if these are the IRAP response options. Based on the current results, it is possible to suggest that a behavioral bias to relate happy faces and true have emerged in the course of the IRAP trial types that presented such a combination (i.e., trial-types 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some of the earliest IRAP publications noted that response times on an IRAP may be influenced by general verbal biases typically found in natural languages, such as the tendency in English to respond "True" more quickly than "False" (Barnes-Holmes, Murphy et al, 2010, p. 62). Indeed, recent evidence indicates that IRAP effects may be influenced by these types of verbal biases and related variables (e.g., Finn et al, 2016;Maloney & BarnesHolmes, 2016;O'Shea, Watson, & Brown, 2016). On balance, the impact of such variables on the predictive validity of the IRAP has yet to be determined, and it is indeed possible that the sensitivity of the IRAP to natural-language biases contributes towards its relatively strong predictive validity (see Vahey et al, 2015).…”
Section: The Mdml Framework For Rft 12mentioning
confidence: 99%
“…Thus, controlling the direction and magnitude of one's IRAP effects seems to be relatively more difficult to achieve when compared with alternative indirect procedures. Critically, however, support for this claim necessitates future research in which the relative sensitivities to manipulation of IRAP, IAT, and AMP effects and other newly introduced indirect procedures (e.g., De Houwer et al, ; O'Shea, Watson, & Brown, ) are directly compared. Surprisingly, past work has tended to focus on the degree to which a single implicit measure can be faked and, in some instances, compared performances on indirect procedures with those on direct procedures.…”
Section: Discussionmentioning
confidence: 99%